Energy Management System for a canning plant - Vásquez Araya, Germán (2020)
This document summarizes the development of an energy management system based on the ISO 50001:2018 standard, for the main plant of a canned seafood company. The process is described from the initial stage where detail the background, the problem, the theory, and other aspects, then is describe and characterize what is an energy management system (EnMS) (ISO, 2018). and finally develops a proposal of the management system for the company under study. Where the implementation of the EnMS predicts a reduction in the annual turnover of 7.48 % that represents annual benefits of USD 175,137.09 for this case.